Analisis Penerapan Metode PDCA Untuk Meminimalisir Komplain Delaminasi Produk Oilpack Di PT XYZ - Nazwa Febriyan; Arrahmah Aprilia; Alfred Setyahadi (P3M Politeknik Negeri Media Kreatif, 2025)
This study aims to analyze the effectiveness of implementing the PDCA (Plan-Do-Check-Act) method in reducing delamination complaints in Oilpack products at PT XYZ. Delamination is a type of defect that significantly affects product quality and customer satisfaction. Through the PDCA stages, this research identifies the main causes of delamination, such as raw material quality and inconsistencies in the production process. Corrective actions were then implemented, including improved quality control and employee training. Evaluation was conducted by comparing complaint data before and after the improvements. The results show a decrease in the number of complaints, indicating that the PDCA method is effective in enhancing quality control and production process efficiency. Therefore, PDCA is considered an appropriate approach for continuous improvement efforts in the manufacturing industry.